1999
DOI: 10.1002/(sici)1097-4547(19990115)55:2<261::aid-jnr14>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of cellular prion protein (PrPc) at the neuromuscular junction

Abstract: We examined the localization of the normal cellular isoform of prion protein (PrPc) in mammalian skeletal muscle. Using two anti-PrP antibodies, the neuromuscular junction (NMJ) was preferentially stained after immunohistofluorescence. The mouse, hamster, and human NMJ displayed a fluorescent signal specific for PrPc. Postembedding immunoelectron microscopy analysis performed in the mouse muscle showed that the PrPc-specific colloidal gold immunolabelling was concentrated over the sarcoplasmic cytoplasm. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Although HY TME was also detected in the submandibular and cervical lymph nodes at 1 week postinfection, the absence of PrP Sc in the spinal cord at 5 weeks postinfection is inconsistent with TME neuroinvasion of the brain stem via the sympathetic nervous system. HY TME entry into CN XII may occur at the neuromuscular junction since PrP C is localized to subsynaptic areas of the postsynaptic and presynaptic cells (3,22). It is possible that PrP Sc can bind to PrP C at the neuromuscular junction and allow PrP Sc entry into the nerve terminal.…”
Section: Fig 6 Prpsupporting
confidence: 73%
“…Although HY TME was also detected in the submandibular and cervical lymph nodes at 1 week postinfection, the absence of PrP Sc in the spinal cord at 5 weeks postinfection is inconsistent with TME neuroinvasion of the brain stem via the sympathetic nervous system. HY TME entry into CN XII may occur at the neuromuscular junction since PrP C is localized to subsynaptic areas of the postsynaptic and presynaptic cells (3,22). It is possible that PrP Sc can bind to PrP C at the neuromuscular junction and allow PrP Sc entry into the nerve terminal.…”
Section: Fig 6 Prpsupporting
confidence: 73%
“…In the present study, PrP Sc deposition was found in nerve fibers and skeletal muscle cells of the tongue. The normal isoform of the prion protein, PrP C , has been demonstrated to spread within nerve fibers by axonal transport (5) and is located in synapses, including subsynaptic areas in both the presynaptic and postsynaptic cells of the NMJ (2,15). Since PrP C is required for PrP Sc formation (7), we propose that the NMJ is a site for PrP Sc formation and/or PrP Sc spread between skeletal muscle cells and axon terminals.…”
Section: Discussionmentioning
confidence: 94%
“…In this case, PrP Sc spread to, and accumulation in, skeletal muscle cells in the tongue following intracerebral inoculation could be due to TME agent replication in the brain and subsequent anterograde transport within the hypoglossal nerve, which provides motor innervation to the lingual muscles. PrP Sc may spread across the NMJ and enter skeletal muscle cells, where additional TME agent replication can occur, since PrP C is also expressed in skeletal muscle cells (15,29). This hypothesis is supported by studies that describe (i) the spread of the prion agent in both the anterograde and retrograde directions between synaptically linked nerve cell groups in the central nervous system (4, 12, 13, 27), (ii) the retrograde transport of the HY TME agent from the tongue to the brain in the hypoglossal nerve following intratongue inoculation (3), and (iii) prion infectivity in skeletal muscle of transgenic mice that express PrP C in myocytes (6).…”
Section: Discussionmentioning
confidence: 99%
“…It was postulated that the HY TME agent could spread from the motor nerve endings into the muscle cell via the synapse at the neuromuscular junction. Ultrastructural localization of the cellular isoform of the prion protein, PrP C , determined that it is present on both the presynaptic nerve terminal and postsynaptic muscle cell membrane (25), suggesting that both locations are potential sites of PrP Sc formation. Since the prion agent can undergo transynaptic spread between neurons, the distribution of the prion protein in muscle is consistent with the neuromuscular junction acting as a peripheral synapse for cell-to-cell spread of the prion agent.…”
mentioning
confidence: 99%